Sistem Persediaan Multi Item dengan Kendala Investasi dan Luas Gudang - Elisa Kusrini (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
In practice, most inventory system accommodate more than one type of item.Under this situation the analysis of inventory problem is approached by treating each type of item independently.The problem becomes complicated when constrains are imposed in inventory system.Constrains normally arise because scarce of resources exist such as capital,storage space, and equipment capacities. This paper considered a multi item inventory system with 2 constrains: working capital and storage space restrictions.The Lagrangian method and The LIMIT technique is utilized to obtain optimal order quantity solution for constraining conditions.While The Lagrangian method transforms a constrained optimization problem into an unconstrained problem for higher dimension,The LIMIT Technique determines the relation of agggregate EOQ requirements to the limited resource available and revises all the lot sizes by the same proportion to bring the aggregate EOQ resources requirements within the limit. A case study of a multi item inventory system with constrains at PD Taru Martani Yogyakarta has been presented in this paper. Keywords : multi item inventory system, constrains, the Lagrangian method, the LIMIT technique, optimal (economic) order quantity.